Activation of Farnesoid X Receptor impairs the tumor-promoting function of breast cancer-associated fibroblasts. (28th November 2018) - Barone, Ines; Vircillo, Valentina; Giordano, Cinzia; Gelsomino, Luca; Győrffy, Balázs; Tarallo, Roberta; Rinaldi, Antonio; Bruno, Giuseppina; Caruso, Antonella; Romeo, Francesco; Bonofiglio, Daniela; Andò, Sebastiano; et al.
Abstract: Cancer-associated Fibroblasts (CAFs), the principal components of tumor microenvironment, play multiple role in breast cancer progression. We have previously shown an oncosuppressive role of the nuclear Farnesoid X Receptor (FXR) in mammary epithelial cancer cells, here we assessed whether FXR activation may affect CAF tumor-promoting features. We showed that FXR is expressed in human CAFs isolated from four patients and treatment with the selective FXR agonist GW4064 decreased CAF migration, stress-fiber formation and contractility. RNA-sequencing highlighted cell movement and pathways known to govern cell cytoskeleton organization and migration among the most down-regulated functions and ingenuity canonical pathways upon GW4064 treatment. FXR activation reduced expression of different secreted factors. Coculture experiments revealed a reduced growth and motility of breast cancer cells treated with conditioned-media derived from GW4064-treated CAFs. Increased FXR levels in bulk tumors correlated with a longer patient survival. Our results evidence that FXR activation inhibits tumor-stimulatory activities of CAFs by impacting their mechanical properties and their paracrine signaling repertoire, suggesting that nuclear FXR ligands, by targeting both neoplastic cells and supportive stroma, may represent a promising avenue for the future management of breast cancer. Highlights: Activated FXR impairs the dual tumor-promoting role of breast CAFs. Activated FXR inhibits migration, stress fibers and contractility of breast CAFs. Activated FXR reduces the expression of soluble factors secreted from breast CAFs. FXR overexpression in breast tumor bulk predicts a better prognosis for patients. Targeting FXR in breast cancer epithelial/stromal cells may be of therapeutic value.